KNOWLEDGE MANAGEMENT ARCHITECTURE - Muslim Muslim (Roqooba Journal of Islamic Education Management, 2022)
Manage knowledge is actually how the organization manages staff, so that knowledge managementis how people from different places start talking to each other, which is now popular with the label learning organization. Expected with implementation knowledge management system will be able to improve the performance of Higher Education so that it has a competitive advantage in facing global competition. Knowledge management is basically a view that information is power, but now it is proven that ownership of information is not enough, but more importantly how the information is judged so that it becomes an idea, and the idea is then given context so that it becomes knowledge. Because the position of knowledge is so important in context that it becomes knowledge. To maintain a sustainable competitive advantage, organizations can do this by adding new knowledge. The combination of old and new knowledge creates new uniqueness which ultimately creates opportunities for knowledge synergies. Knowledge can be a long-lasting competitive advantage when an organization knows more about something than its competitors. Not like resources other traditional methods that can be reduced when used, knowledge will actually increase when used. The more frequently used knowledge, the more valuable it will be to the organization.